If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (X + 25) = (2x + 10) Reorder the terms: (25 + X) = (2x + 10) Remove parenthesis around (25 + X) 25 + X = (2x + 10) Reorder the terms: 25 + X = (10 + 2x) Remove parenthesis around (10 + 2x) 25 + X = 10 + 2x Solving 25 + X = 10 + 2x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-25' to each side of the equation. 25 + -25 + X = 10 + -25 + 2x Combine like terms: 25 + -25 = 0 0 + X = 10 + -25 + 2x X = 10 + -25 + 2x Combine like terms: 10 + -25 = -15 X = -15 + 2x Simplifying X = -15 + 2x
| (7+2)x(9-4)= | | -9+8r=r+7+3r | | 4(3x+4)+53=17x+12-5x+57 | | 1234(4321-5432)+123a=6000 | | (-6w^2+4w-3)+(7w^2+2w+1)= | | (4+2i)-(6-8i)= | | -y=9(3.2)+33 | | 6x+24x-5=6(5x+7) | | -10=+14v+14v | | 3(x+100)=8x | | 108-4-6B=24-4 | | 6x^2-11X=-5X | | 7x+8x=125 | | 3(x-2)=14+4x | | -5(-3x-5)=85 | | 1234(4321-3456)=6000 | | K+8-8k=-152 | | p-2=-8+2p | | 3timesx=40 | | 7x+5x-1=3(4x+2) | | 12+n=-9 | | 16x-(2x-8y)= | | 0.6r-0.12=1.8 | | 5x-5+6x=-71 | | 9x+26=16 | | -2(n-3)=-12 | | 2c=1 | | 15x^2-19xy=-6y^2 | | -7z+42=-70 | | 3d^2-44d+140=0 | | 3x+1+5x=17+15+7x | | 7[3-(4+2x)]-2x=-9+2(1-8x) |